What makes a big demonstration? Exploring the impact of mobilization strategies on the size of demonstrations. (4th March 2019) - Somma, Nicolás M.; Medel, Rodrigo M.
ABSTRACT: Massive demonstrations are the staple of powerful social movements, but research on the factors affecting the size of demonstrations (in terms of number of attendants) is almost nonexistent. Why do some demonstrations pack long avenues with masses of people while other ones barely fill a street corner? Combining resource mobilization, political opportunity, and framing theories, we argue that mobilization strategies – the sequence of decisions and actions taken by protest organizers before staging a protest – shape demonstration size. Multivariate models with 937 Chilean demonstrations between 2000 and 2012 show that demonstrations are larger when they display more demands (especially universalistic demands), target the national government, attract more organizations (especially umbrella organizations), and mobilize cohesive groups with broad public support. We reinforce the internal validity of our argument using interviews with movement leaders and secondary research on Chilean society.